Yiqihuoxuejiedu Formula Inhibits Vascular Remodeling by Reducing Proliferation and Secretion of Adventitial Fibroblast after Balloon Injury. (27th May 2014) - Zhao, Ming-Jing; Wu, Ai-Ming; Wang, Jie; Chang, Hong; Gao, Yong-Hong; Liu, Hui-Min; Lv, Xi-Ying; Lei, Huan; Sun, Qing-Qin; Xu, Ying; He, Ying-Kun; Wang, Shuo-Ren
Abstract : Vascular remodeling occurs in atherosclerosis, hypertension, and restenosis after percutaneous coronary intervention. Adventitial remodeling may be a potential therapeutic target. Yiqihuoxuejiedu formula uses therapeutic principles from Chinese medicine to supplement Qi, activate blood circulation, and resolve toxin and it has been shown to inhibit vascular stenosis. To investigate effects and mechanisms of the formula on inhibiting vascular remodeling, especially adventitial remodeling, rats with a balloon injury to their common carotid artery were used and were treated for 7 or 28 days after injury. The adventitial area and α -SMA expression increased at 7 days after injury, which indicated activation and proliferation of adventitial fibroblasts. Yiqihuoxuejiedu formula reduced the adventitial areas at 7 days, attenuated the neointima and vessel wall area, stenosis percent, and α -SMA expression in the neointima, and reduced collagen content and type I/III collagen ratio in the adventitia at 28 days. Yiqihuoxuejiedu formula had more positive effects than Captopril in reducing intimal proliferation and diminishing stenosis, although Captopril lowered neointimal α -SMA expression and reduced the collagen content at 28 days. Yiqihuoxuejiedu formula has inhibitory effects on positive and negative remodeling by reducing adventitial and neointimal proliferation, reducing content, and elevating adventitial compliance.